Peran Pendidikan Agama Islam dalam Membangun Sikap Toleran dan Damai di Kalangan Peserta Didik - Hasan, Nur; Cholid, Nur; Hamzah, Ghufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia’s multicultural society, characterized by religious, cultural, and ethnic diversity, presents both opportunities and challenges for social cohesion. In recent years, increasing tendencies toward intolerance and exclusivist religious attitudes among students have raised concerns regarding the effectiveness of religious education in fostering peaceful coexistence. This study aims to analyze the role of Islamic Religious Education (Pendidikan Agama Islam/PAI) in shaping tolerant attitudes among students within a multicultural social context. This research employs a qualitative descriptive approach to explore how PAI contributes to the formation of students’ tolerant and peaceful attitudes. Data were collected through classroom observations, in-depth interviews with Islamic education teachers and students, and analysis of instructional documents. The findings indicate that PAI plays a significant role in cultivating students’ tolerance when learning processes emphasize dialogical interaction, contextual understanding of religious teachings, and appreciation of diversity. Students who engage in reflective and inclusive PAI learning demonstrate greater openness toward differences and a stronger commitment to peaceful social relations. The study concludes that Islamic Religious Education, when implemented through contextual and dialogical pedagogical approaches, functions not merely as a medium for transmitting religious knowledge but as a transformative educational space for developing tolerant attitudes in multicultural societies. These findings underscore the importance of reorienting PAI learning toward inclusivity and social harmony to address contemporary challenges of diversity and pluralism.